Standards of hygiene for ultrasound-guided core cut biopsies of the breast - Heil, Jörg; Hug, Sarah; Martiny, Heike; Golatta, Michael; Feisst, Manuel; Madjar, Helmut; Bader, Werner; Hahn, Markus (Ultraschall in der Medizin - European Journal of Ultrasound, 2018)
Purpose The aim was to obtain an overview of the hygiene measures undertaken during ultrasound guided core cut biopsies of the breast by experts certified by the German Society for Ultrasound in Medicine in order to derive recommendations for clinical routine, taking into account the available literature and the lack of evidence based guidelines.Materials and Methods A survey was conducted with all members of the levels I to III of the breast ultrasound working group of the German Society for Ultrasound in Medicine. The estimation of the risk of infection after a core cut biopsy of the breast was asked for as well as the hygiene measures undertaken in practice to avoid infection.Results The risk of infection after a core cut biopsy of the breast was estimated to be one per thousand (median value). The most commonly performed hygiene measures were a spray, wipe, spray desinfection (98.1 %) and the use of sterile gloves (54.7 %).Conclusion Due to the very low risk of infection we recommend the routine use of gloves and an adequate skin disinfection. Contact of the transducer or of an unsterile contact medium with the biopsy needle is considered highly unlikely und should be avoided.Ziel Ziel dieser Arbeit war es, eine Übersicht von über die Deutsche Gesellschaft für Ultraschall in der Medizin zertifizierten Experten über durchgeführte Hygienemaßnahmen bei der ultraschallgeführten Stanzbiopsie der Mamma zu erhalten, um daraus in Kenntnis der vorliegenden Literatur und mangels evidenzbasierter Leitlinien aktuelle Handlungsempfehlungen für die klinische Routine abzuleiten.Material und Methode Es wurde eine Umfrage unter allen Mitgliedern der Stufe I–III des Arbeitskreises Mamma-Sonografie der Deutschen Gesellschaft für Ultraschall in der Medizin durchgeführt. Erfragt wurde die Einschätzung eines Infektionsrisikos bei der Stanzbiopsie der Mamma und welche Hygienemaßnahmen in der Praxis durchgeführt werden, um eine Infektion zu vermeiden.Ergebnisse Das Risiko für eine Infektion nach einer Stanzbiopsie der Mamma wurde im Median auf 1 Promille geschätzt. Die häufigsten durchgeführten Hygienemaßnahmen waren eine Sprüh-Wisch-Sprüh-Desinfektion (98,1 %) und die Verwendung steriler Handschuhe (54,7 %).Schlussfolgerungen Aufgrund des sehr geringen Infektionsrisikos empfehlen wir, in der Routine Handschuhe zu nutzen und eine adäquate Hautdesinfektion durchzuführen. Der Kontakt des Schallkopfes oder eines unsterilen Kontaktmediums mit der Biopsie-Nadel wird als äußerst unwahrscheinlich eingeschätzt und sollte vermieden werden.
Keywords: breast ultrasound; core cut biopsy; hygiene; infection